Interchangeable Core And Cavity Plates For Two-Plate Family Injection Mould - Md Ali, Mohd Amran; Mohd Ali, Noorfa Idayu; Abdullah, Zulkeflee; Abu Bakar, Mohd Hadzley; Subramonian, Sivarao; Abdul Aziz, Mohd Sanusi; Abdullah, Abu (Universiti Malaysia Pahang, 2017)
This study modified a two-plate family plastic injection mould to become interchangeable by changing the core and cavity plates using an existing mould base. The plastic parts produced in the modified two-plate family plastic injection mould included tensile, hardness, impact and flexural test specimens. The cavities of the plastic parts were machined at the parting surface of core plate. Meanwhile, the feeding systems including runner and gate system were machined at the cavity plate to ensure molten plastic can be injected in the cavity area. Various factors have been considered during the designing and fabricating process. This is to ensure the process of assembly between mould plate and standard mould parts can be done perfectly. The plastic parts in the family mould were successfully injected after mould was completed assembled and mould trial was performed. The plastic parts which had been ejected from the family injection mould are purposely produced for future research to study the mechanical properties of plastic materials.